Debating secularism: A liberal cosmopolitan perspective - Gülalp, Haldun (Frontiers in Sociology, 2023)
In the classical notion of secularism, privatization of religion is an essential component of freedom and equality between citizens, so that rights are granted to individuals rather than to communities. The currently dominant objections to this notion in the literature are the multiculturalist thesis, primarily expounded by Tariq Modood, and the critique of secularism through the “genealogical” method, associated with Talal Asad and his followers. This article critically assesses these objections and defends the classical notion of secularism from a liberal cosmopolitan perspective. The argument that the classical notion perfectly addresses the questions of freedom of conscience and diversity of belief is further supported by reference to an ignored source, Thomas More's Utopia.